GP-GPU Processing of Molecular Dynamics Simulations - Millán Kujtiuk, Emmanuel (2010)
Graphics Processing Units (GPUs) is an emergent hardware technology potentially suitable for High Performance Applications. In this work GPU processing of Molecular Dynamics (MD) simulations is discussed. An overview of GPU architecture is provided and its main features are outlined. Some relevant atomistic MD applications are processed using GPU hardware. The same applications are simulated using CPU oriented applications as well in order to obtain comparable results. In this case both serial and MPI codes are considered. Wall-clock timing of GPU results obtained with a relatively low-end card are found to be comparable to timing from multiple core clusters.